Anti Diabetic Evaluation of Methanolic Extract of Psoralea corylifolia L. & Psoralea esculenta L. Seeds in Streptozotocin Induced Diabetic Rats and Histopathological Changes in Diabetic Rats Pancreas: A Comparative Study - Singh, Neeraj; Gautam, Girendra K.; Ved, Akash; Shukla, Karuna S. (Natural Products Journal, The, 2022)
Background: Diabetes mellitus is a metabolic disorder which results in a high level of sugar due to inadequacy in insulin secretion. The high sugar level in diabetes is linked to the impairment and dysfunction of the eyes, kidneys, blood vessels, nerves, and heart. In the current research, herbal medicines have been explored because of the side effects associated with oral hypoglycemic therapy of hyperglycemia. Herbal medicines could play a dominant role in the control of diabetes mellitus. Methods: Methanolic extracts of seeds of Psoralea corylifolia L & Psoralea esculenta L have been screened for both in-vitro and in-vivo anti-hyperglycemic roles using streptozotocin-induced diabetic rats. The methanolic extract of both plants was evaluated for pancreatic tissue studies. Results: According to the outcomes, a significant decrease in blood glucose level was observed in the diabetic groups treated with methanolic extracts of Psoralea corylifolia L. seeds. Conclusion: In this study, the methanolic extract of Psoralea corylifolia L. seeds used to evaluate anti-hyperglycemic potential showed appreciably notable and astonishing results when compared with the Glibenclamide. The methanolic extract of Psoralea corylifolia L. seeds has the potential to regulate hyperglycemia in the in-vivo model. Hence, Psoralea corylifolia L. methanol seeds extract may be selected for its anti-hyperglycemic activity.
Keywords: antidiabetic activity